Root Reduction Caused Directly or Indirectly by High Application of Nitrogen Fertilizer Was the Main Cause of the Decline in Biomass and Nitrogen Accumulation in Citrus Seedlings - Runzheng Niu; Yuan Zhuang; Mohammad Naeem Lali; Li Zhao; Jiawei Xie; Huaye Xiong; Yuheng Wang; Xinhua He; Xiaojun Shi; Yueqiang Zhang (Plants, 2024)
Citrus is the largest fruit crop around the world, while high nitrogen (N) application in citrus orchards is widespread in many countries, which results not only in yield, quality and environmental issues but also slows down the establishment of citrus canopies in newly cultivated orchards. Thus, the objective of this study was to investigate the physiological inhibitory mechanism of excessive N application on the growth of citrus seedlings. A pot experiment with the citrus variety Orah (Orah/Citrus junos) at four N fertilization rates (0, 50, 100, and 400 mg N/kg dry soil, denoted as N0, N50, N100, and N400, respectively) was performed to evaluate the changes of root morphology, biomass, N accumulation, enzyme activities, and so on. The results showed that the N400 application significantly reduced the total biomass (from 14.24 to 6.95 g/Plant), N accumulation (from 0.65 to 0.33 g/Plant) and N use efficiency (92.69%) in citrus seedlings when compared to the N100 treatment. The partial least squares pathway model further showed that the decline of biomass and N accumulation by high N application were largely attributed to the reduction of root growth through direct and indirect effects (the goodness of fit under the model was 0.733.) rather than just soil N transformation and activity of root N uptake. These results are useful to optimize N management through a synergistic N absorption and utilization by citrus seedlings.